Acute generalized exanthematous pustulosis induced by icotinib: a case report and literature review - Yang, Wei; Zhao, Jiayu; Niu, Jun (Frontiers in Pharmacology, 2024)
Acute generalized exanthematous pustulosis, an infrequent adverse drug reaction, mainly results from drugs. Clinically, acute generalized exanthematous pustulosis manifests as a high fever, with skin lesions of small monomorphic subcorneal sterile pustules on an erythematous that presents at 1–4 days after medication exposure. The incidence of acute generalized exanthematous pustulosis varies from 3/1, 000, 000 to 5/1, 000, 000, while the mortality rate is typically around 5%. We present a case of a 69-year-old female who developed a diffuse, erythematous, pustular rash over the entire body and exhibited a fever of 38.3°C after 4 days of icotinib therapy. Considering her medication history and the appearance of the lesions, she was diagnosed with acute generalized exanthematous pustulosis and received appropriate treatment. We also conducted a literature review through PubMed to compare similarities and differences between our case and those reported in the literature.